Juridical Analysis of the Division of Inheritance to the Heirs of Different Marriages (Decision Number 435/PDT/2018/PT MDN) - Zakiyah Triyana Hardi; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
In civil inheritance law, a principle applies, namely if someone dies (heir), then by law and immediately his rights and obligations are transferred to his heirs, as long as these rights and obligations are included in the field of property law or in other words rights and liabilities that can be valued in money. The civil inheritance law system has a characteristic that is different from other inheritance law systems, which requires that the heir's inheritance be divided as soon as possible among those who are entitled to the property. In the distribution of inheritance, the heir as the owner of the property has the absolute right to arrange what he wants for his property. This is a consequence of inheritance law as a regulatory law.